2019
DOI: 10.1038/s41467-019-12507-9
|View full text |Cite
|
Sign up to set email alerts
|

The midbody interactome reveals unexpected roles for PP1 phosphatases in cytokinesis

Abstract: The midbody is an organelle assembled at the intercellular bridge between the two daughter cells at the end of mitosis. It controls the final separation of the daughter cells and has been involved in cell fate, polarity, tissue organization, and cilium and lumen formation. Here, we report the characterization of the intricate midbody protein-protein interaction network (interactome), which identifies many previously unknown interactions and provides an extremely valuable resource for dissecting the multiple ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
109
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 53 publications
10
109
0
Order By: Relevance
“…(C) Key linking heatmap colour with observed MS ratio.over time and no clusters were found to have a half-life >50% different from control(Figure 7-source data 1). This agrees with observations that PPP1CB is part of a specific myosin phosphatase and its depletion does not result in defects in furrowing and cytokinesis suggestive of a predominantly non-mitotic role(Capalbo et al, 2019;Takaki et al, 2017;Zeng et al, 2010).The clustering comparison of 2734 phospho-sites from control and PPP1CA/C depleted samples was empirically found to require eight clusters corresponding to early, intermediate, late and stable phosphorylation sites defined inFigure 2 (…”
supporting
confidence: 88%
“…(C) Key linking heatmap colour with observed MS ratio.over time and no clusters were found to have a half-life >50% different from control(Figure 7-source data 1). This agrees with observations that PPP1CB is part of a specific myosin phosphatase and its depletion does not result in defects in furrowing and cytokinesis suggestive of a predominantly non-mitotic role(Capalbo et al, 2019;Takaki et al, 2017;Zeng et al, 2010).The clustering comparison of 2734 phospho-sites from control and PPP1CA/C depleted samples was empirically found to require eight clusters corresponding to early, intermediate, late and stable phosphorylation sites defined inFigure 2 (…”
supporting
confidence: 88%
“…This includes the 4 Rab proteins already involved in cytokinesis (Rab8, Rab11, Rab14, and Rab35) 3 , as well as transmembrane proteins such as chloride channels (CLIC1 and CLIC4, previously localized at the midbody 52 ), adhesion/tethering/signaling molecules (ITGA3, PlexinB2, ICAM1, BST2, and CD44) and tetraspanins (CD9, CD9-P1, and TM4SF1) whose potential functions during cytokinesis will be studied in the future. These three points are key improvements, when comparing with previous proteomes of intercellular bridges, which already proved to be seminal in identifying essential proteins in cytokinesis 44,53 . Of note, 68 and 29% of the final list of Skop et al (160 proteins from CHO cells) were respectively present in our Total Flemmingsome (1732 proteins) and Enriched Flemmingsome (489 proteins) ( Supplementary Data 1, TAB6).…”
Section: Discussionmentioning
confidence: 99%
“…In functional terms, targeting of ALIX to ACBs may sequester a particular subpopulation of this protein away from the midbody, contributing to the checkpoint-dependent abscission delay. Such targeting is predicted to be halted when the checkpoint is satisfied and phosphatases such as PP1 counteract pAurB and thus pppCHMP4C (Bhowmick et al, 2019; Capalbo et al, 2019). Previous studies have demonstrated that ALIX must be activated by phosphorylation on its autoinhibitory C-terminal tail in order to bind CHMP4 proteins and to function in abscission (Sun et al, 2016; Zhai et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Once the abscission checkpoint is satisfied, cytokinetic abscission is mediated by the Endosomal Sorting Complexes Required for Transport (ESCRT) pathway, at least in transformed, cultured mammalian cells (Carlton and Martin-Serrano, 2007; Gatta and Carlton, 2019; Morita et al, 2007; Vietri et al, 2020). The ESCRT adaptor protein CEP55 provides an ESCRT recruiting platform (Carlton and Martin-Serrano, 2007; Morita et al, 2007) at a protein-rich structure called the Flemming body (Capalbo et al, 2019; Skop et al, 2004) centrally located within the midbody. CEP55 forms rings on either side of the Flemming body and recruits the early-acting ESCRTs TSG101 (a component of the ESCRT-I complex) and ALIX through a shared binding site (Lee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%